CONTROLLING IN THE SYSTEM OF ENSURING THE FINANCIAL AND ECONOMIC SECURITY OF THE ENTERPRISE - KELMANOVICH, Alexander (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The need to improve the monitoring and controlling subsystem tools in the enterprise financial and economic security management system is substantiated, which will contribute to increasing the effectiveness of management decisions made to reduce the impact of existing risks. The foundations and basic components of ensuring the financial and economic security of an enterprise are investigated, proving the need to identify the entity's own concept of strategic management, which takes into account the specifics of doing business, as well as the conditions of the business environment. The reasons for the importance of improving approaches to controlling in managing the financial and economic security of an enterprise are determined. In the context of the existence of current, operational and strategic controlling of the financial and economic security of an industrial enterprise, its basic functions are characterized, which contribute to the implementation of the development strategy. The current concept of controlling in the enterprise management system is substantiated, in particular in ensuring financial and economic security. The tasks and approaches to the formation of an effective information and analytical basis are substantiated, which ensures the mutual coordination of functional controlling measures in the aspect of each component of the financial and economic security of the enterprise.The methods and tools used during controlling processes in the system of ensuring the security of the enterprise are studied. The influence of marketing of financial and economic security on the effectiveness of the subsystem of controlling and monitoring in the system of strategic management of the enterprise is proven.
Keywords: controlling; monitoring; financial and economic security; strategic management of the enterprise; marketing